THE MODERATING ROLE OF TRAINING ON THE RELATIONSHIP BETWEEN STRATEGY MANAGEMENT, INFORMATION TECHNOLOGY MANAGEMENT AND ORGANIZATIONAL PERFORMANCE OF SHARJAH POLICE - Abdulhabib, Abdulla Awadh Abdulla; Al-Dhaafri, Hassan Saleh (PEOPLE: International Journal of Social Sciences, 2019)
This study’s primary objective is to examine the role of training on the relationship between strategy management, information technology (IT) management, and organizational performance. The study proposed the study model based on theoretical basis and a review of literature with the underpinning model being the Resource-Based View of the Firm (RBV), Knowledge–Based View (KBV) and innovation theories. The analysis of data was conducted on the effects of IT management and strategy management on the organizational performance of three hundred and forty-one (341) Sharjah Police in Emirate of Sharjah, UAE, to which the questionnaire survey copies were distributed to. A total of two hundred and forty-five (245) questionnaires were retrieved and tested with the help of SPSS. The analysis results indicated the positive and significant effects of both IT management and strategy management on the performance of Sharjah Police departments. The study enumerated recommendations for the effective IT management and strategy management implementation in the Sharjah Police and confirmed the underpinning theories applicability to the context.